The plasma lactate response to exercise and endurance performance: relationships in elite triathletes - Hoogeveen, A. R.; Schep, G. (International Journal of Sports Medicine, 1997)
The lactate response to exercise has been studied thoroughly during the last decades and it has been described using a variety of terms and definitions. Numerous investigations observed close relationships between the lactate response and endurance performance. The main question in this study was which of the various lactate responses during incremental exercise described in the literature was the best indicator of endurance performance. The plasma lactate response (PLR) was assessed during an incremental exercise test on 13 male elite triathletes (age 25.5+/-5.8 yrs; HT 179.7+/-5.4 cm; WT 71.3+/-4.7 kg) on a bicycle ergometer. The load was started at 2.5 W/kg and increased by 40 W every 4 min. We evaluated the following PLR-parameters: the workloads at the fixed lactate levels of 2, 3, 4, 5, 6, 7, and 8 mmol/l which were assessed by extrapolation from a workload-lactate-heart rate curve (P2, P3, P4, P5, P6, P7, P8 respectively), the lactate threshold which was defined as the workload at the point at which a non-linear increase of blood lactate occurred (Plt), and the workload at the lactate level that was 1 mmol/l above the baseline (P + 1). Four to seven weeks after the laboratory test, heart rate and lactate levels were assessed during a 40-km long time trial on a bicycle. Two parameters were considered as indicative of athletic performance: the road racing time (Tt), and the workload extrapolated from the workload-lactate-heart rate curve at the heart rate and lactate levels observed during the time trial (Pt). Only P2 showed a significant correlation with Tt (r=-0.65; p < 0.05; se = 72.5 s). Multiple regression analysis with the anthropometric parameters height and weight as additional independent parameters did not change the predictive value. We concluded that for predicting the cycling performance of similarly well-trained subjects the predictive value of PLR is negligible.